SPACE ARRANGEMENTS INFLUENCING BEAN CULTURE IN SYSTEM OF CONVENTIONAL SOWING - SCHAMME, José Antonio (Scientia Agraria, 2002)
A field trial was carried out at Cangüiri Experimental Station of Paraná Federal University from January, 13th April, 18th 2000. The objective was to determine the most adequated spatial arrangement for bean in tillage system. The variety used was FT BIONOBRE. The experimental design used to analyse yield, grain weight, seeds per pod and apparent harvest index was randomized complete block with four treatments (0.30m, 0.40m, 0.50m and 0.60m row width) arranged in strips and six replications. In order to evaluate the morphological characteristics, a randomized complete block for width row, with developmental stages V4, R6, R7, R8 and R9 split plot on it, was used. Plots were formed by tem rows with 5.0 m lenght. Population was standardized by thinning in the four width rows, in wich remained about 8.1; 10.8; 13.5; and 16.2 plants.m-1. Tendency of leaf area increasing and apparent harvest index decreasing was observed when row width was increased. Greater leaf area associated with low water availability contributed to diminish the yield. Yield in 0.30 m row width was greater than the yield in 0.60 m.